The Physical Quality Test of Anti-Acne Gel Preparations of Shallot Skin Extract (Allium cepa L) and Antibacterial Activity Test Against Propionibacterium acne Bacteria - Nafisah Isnawati; Dina Trianggaluh Fauziah (Journal of Pharmaceutical and Health Research, 2023)
Shallot skin is a simplicia that contains secondary metabolites such as polyphenols, saponins, terpenoids, alkaloids, and flavonoids that are efficacious as antibacterials. The purpose of this research was to formulate and evaluate the physical quality of shallot skin extract gel preparation (Allium cepa L.) and test the anti-bacterial activity against bacteria. Propionibacterium acne is one of the causes of acne. The research method is experimental research by making a gel preparation formula of shallot skin extract then physical testing and testing antibacterial activity against Propionibacterium acnes bacteria. The results showed that the shallot skin extract gel preparation had good homogeneity, gel texture, and a distinctive aroma of shallots and a slightly brown-yellow color. The pH and spreadability tests fulfill the gel preparation requirements. The adhesion and viscosity tests of the three formulas did not reach the requirements of gel preparations. The inhibitory power of the gel preparation is in a strong category. In conclusion, shallot skin extract gel preparation has inhibition against Propionibacterium acnes bacteria.